From falling behind to catching up : a country economic memorandum for Malawi - Record, Richard (Directions in development (Washington, D.C.). Public sector governance., 2018)
Despite decades of development efforts supported by significant amounts of foreign aid, Malawi has experienced weak and volatile economic growth performance over a sustained period of time. Malawi's growth remains an outlier even compared to its geographically and demographically similar peers. Moreover, growth has been distributed unequally, with little impact on poverty. Per capita income has improved only minimally in the 50 years since independence, and Malawi now has one of the lowest per capita incomes in the world. This publication aims to improve readers' understanding of the puzzle of Malawi's development performance and identify ways for the country to achieve robust growth and stay on a stable growth path that helps the poor. The book places a strong emphasis on assessing Malawi's growth experience since independence from a comparative international perspective. It seeks to benchmark Malawian outcomes on growth, structural change, and transformation against peers and explores possible reasons for divergence from international trends. The book also puts deeper drivers of economic growth at the center of the discussion, looking in particular at the institutions and policies that may have affected Malawi's growth outcomes and ones that could help Malawi avoid macroeconomic instability in the future. This book first begins by discussing Malawi's macroeconomic situation and challenges in fiscal management, reviewing and drawing lessons from the instability, slippages, and shocks Malawi has experienced since independence. Second, given how critical the agricultural sector is to poverty reduction in Malawi, the overview explores the current state of agricultural markets. Third, looking at the factors that may constrain higher growth in the future, challenges in private sector development and job creation are discussed. Finally, building on the analysis of challenges, the book concludes with a summary of policy recommendations aimed at helping Malawi begin catching up with its peers.